Gender Mainstreaming and Women Development in Bushenyi District, Uganda - Naturinda , Ronah; Edabu , Paul (African Journal of Education,Science and Technology (AJEST), 2023)
A lot of interventions have been implemented by the central government, NGOs and District Local Service on gender mainstreaming. The attainment of gender equality has been limited, despite remarkable progress in Bushenyi district. The paper investigates the influence of gender mainstreaming on development of women in Bushenyi district, Uganda. The descriptive survey design using comparative approaches was used. The study used Slovene’s formula to obtain (251) respondents. The study used purposive sampling technique involving 87 Kyamuhunga,61 Kakanju, 30 Kyeizoba and 73 Bitooma, using two sets of questionnaires. Quantitative analysis specifically means and student t-test was used. The study established that (2.306 = Low) revealed that gender mainstreaming approaches were low. The study established that implementation of equity, efficiency, policy, anti-poverty and empowerment approaches was low in the district. The study revealed that (2.385 = low) as the overall mean on women development was low in Bushenyi district. The study also revealed that there was significant difference in the level of Gender Mainstreaming and Development (GMD) of women in Bushenyi district, Uganda. The study concludes that female practical interests were still low as compared to their male counterparts in terms of gender mainstreaming and development in Bushenyi district, Uganda. The male had more powers in the development process in Bushenyi district. The study recommends awareness on changing institutional, structural, and organizational policies affecting gender. The ministry of Gender, Labour and Social Development should prioritize increasing gender awareness by engaging on social mobilization and gender sensitization. Gender issues should be incorporated during meetings, seminars and workshops. Women should be involved at any level of developing solutions in society.